Issues of the Professional Transformations of the Internet Journalist - AVETISYAN, ARMEN (Bulletin of Yerevan University B: Philology, 2021)
Internet journalism was formed on the boundary of 20-21 centuries as an independent sector of the journalistic activities. Development and emergence of the cable and satellite television, personal computers, mobile devices created theconditions for spreading the information in an incredibly unprecedented scale and speed. The profession of the journalist also saw some changes. The perspective of the “universal journalist” is discussed more and more often in professional circles, in which the ability to use information technology becomes the most important quality. The Internet has expanded the journalist’s toolbox, providing with not only new capabilities of information search and unlimited spectrum of information sources, but also new tools for professional and interactive communication with the audience, as well as more effective ways for the professional development and self-realization.
Keywords: internet journalist, media, multipurpose journalist, transforming journalism, interactivity, feedback, journalistic ethics